Comparison of the Cigarette Dependence Scale with Four Other Measures of Nicotine Involvement: Correlations with Smoking History and Smoking Treatment Outcome in Smokers with Substance Use Disorders - Rohsenow, Damaris J. (2013)
The Cigarette Dependence Scale (CDS) was developed to assess principal aspects of smoking dependence. In a French longitudinal survey, CDS showed stronger relationships to urge and change in smoking rate than the Fagerström Test for Nicotine Dependence (FTND). Neither measure predicted abstinence at follow-up in that survey but there was no treatment or cessation induction. The present study investigated concurrent and predictive validity of the CDS in a treatment population by comparing the CDS to the FTND and other measures of tobacco involvement as (1) a correlate of smoking and cessation history and (2) a predictor of short-term smoking abstinence among smokers with substance use disorders (SUD) receiving smoking treatment. METHODS: Smokers (10+ cigarettes per day) in substance treatment received brief advice and nicotine patch for 8 weeks; half also received contingent vouchers for smoking cessation. Assessments were conducted pretreatment and 7, 14 and 30 days after treatment initiation, with abstinence verified biochemically. RESULTS: At baseline (n = 305), the 12-item and 5-item CDS versions showed excellent and marginal reliability, respectively. FTND shared 43 and 61% of variance with CDS-12 and CDS-5, respectively. FTND and CDS scales correlated positively with cigarettes per day, and negatively with time to first cigarette, motivation to quit and age at first daily smoking. Only CDS correlated with number of past quit attempts. Neither CDS nor FTND predicted abstinence within treatment, unlike the motivation measure and time to first cigarette. CONCLUSION: In moderate-heavy smokers with SUD in smoking treatment in the U.S., the CDS is largely equivalent to the FTND as an indicator of tobacco dependence but the CDS-5 is less reliable. Motivation was the most consistent predictor of outcome, and time to first cigarette was the only tobacco dependence measure that predicted smoking abstinence during treatment.